2020
DOI: 10.2196/16527
|View full text |Cite
|
Sign up to set email alerts
|

The Personal Health Network Mobile App for Chemotherapy Care Coordination: Qualitative Evaluation of a Randomized Clinical Trial

Abstract: Background Cancer care coordination addresses the fragmented and inefficient care of individuals with complex care needs. The complexity of care coordination can be aided by innovative technology. Few examples of information technology-enabled care coordination exist beyond the conventional telephone follow-up. For this study, we implemented a custom-designed app, the Personal Health Network (PHN)—a Health Insurance Portability and Accountability Act-compliant social network built around a patient … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Adopting the lens of Feather et al's (2016) concept of usability inquiry, five themes emerged from the literature published in the past decade. Several studies show that people with cancer appreciated the role of technology in helping them to learn new information about being unwell and their body's response as they were dealing with it (Gustavell et al, 2020;Hauffman et al, 2020;Ngo et al, 2020;Ownsworth et al, 2020;Ure et al, 2020), which was found to be particularly helpful post-diagnosis or at the commencement of cancer treatment. Evidence shows that people with cancer and their family caregivers may not process information when provided by their healthcare team due feeling emotionally overwhelmed and overloaded with new information (Den Bakker et al, 2018;Ream et al, 2013) or perceived as being poorly co-ordinated (Lubberding et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Adopting the lens of Feather et al's (2016) concept of usability inquiry, five themes emerged from the literature published in the past decade. Several studies show that people with cancer appreciated the role of technology in helping them to learn new information about being unwell and their body's response as they were dealing with it (Gustavell et al, 2020;Hauffman et al, 2020;Ngo et al, 2020;Ownsworth et al, 2020;Ure et al, 2020), which was found to be particularly helpful post-diagnosis or at the commencement of cancer treatment. Evidence shows that people with cancer and their family caregivers may not process information when provided by their healthcare team due feeling emotionally overwhelmed and overloaded with new information (Den Bakker et al, 2018;Ream et al, 2013) or perceived as being poorly co-ordinated (Lubberding et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some partners of people with breast cancer referred to it as an obligation which could invoke guilt if they did not complete their assigned activities. Conversely, other studies found that technology was easily embedded in their daily routine and personal schedule (Maguire et al, 2020;Ngo et al, 2020;Hauffman et al, 2020), appreciating the option to engage at a time and pace that suited them (Song et al, 2015;Smith et al, 2020a;Drott et al, 2016) and enabled the person with cancer to plan their schedule (Mohsen et al, 2021;Crafoord et al, 2020). Participants with cancer also found benefit from eHealth technology in that they gained time in their own lives and did not have to travel to their treatment centre for supportive care, whereby people with cancer perceived an additionalreduced burden on their family caregivers (Dalby et al, 2021;Ownsworth et al, 2020).…”
Section: Alignment and Integration Of Ehealth Technology Into Daily Lifementioning
confidence: 99%
See 3 more Smart Citations